The Role of Inflation and Foreign Investment on Economic Growth in Banten Province - Rasam, Fadli; Murti, Wahyu; Rozali, Muhammad (Formosa Journal of Sustainable Research, 2024)
Inflation and foreign investment have an important impact on economic growth in a province, including Banten Province. Investment can open up extensive employment opportunities. This research method uses a literature review method. Literature review is an important stage in research which aims to collect, analyze and summarize information from various sources relevant to the research topic. The research results show that high inflation can reduce people's purchasing power, so that household consumption can decrease. When inflation is out of control, people will be more careful in spending, which can affect demand for goods and services. High inflation rates can create uncertainty in the market, thereby reducing investors' interest in investing. Conversely, low and stable inflation can encourage greater investment